Using spatial games to model dynamic evolutionary systems. Issue 3 (4th May 2018) - Kuang, Yan; Ben-Arieh, David; Wu, Chih-Hang; Zhao, Songnian
ABSTRACT: Modelling the dynamics of evolutionary competing species on a physical grid is a challenging modelling problem. This paper presents a novel modelling approach for synthesizing evolutionary dynamics of competing species using a spatial game perspective. This modelling approach describes the movement of players ('species' in our context) across a lattice. The model is based on a payoff function which controls the move likelihood and direction of the players ('predators' and 'preys'). Using simulated results, the paper provides a comparison between the spatial game model and an existing predator-prey dynamic model. Finally, a case study is performed to illustrate the application of this formalism and validate the model.